Pembinaan Pendidikan Akhlak di Madrasah Aliyah Miftahussalam Medan - Hadi Saputra Panggabean; Sakban Lubis; Iswanto Ariga (Medan Resource Center, 2025)
This study investigates the development of character education at the Private Madrasah Aliyah Miftahussalam Medan by examining its conceptual foundation, implementation patterns, and effectiveness within the school environment. The research addresses the central question of how Islamic ethical principles are integrated into daily educational practices to shape students’ moral character. Using a qualitative design, data were collected through classroom observations, interviews with teachers and students, and documentation of institutional programs. The findings reveal that character formation is carried out through structured religious activities, teacher role modelling, extracurricular programs, and environmental habituation that reinforces discipline, respect, and spiritual awareness. The study identifies institutional commitment and teacher exemplarity as supporting factors, whereas challenges arise from limited facilities, inconsistent program implementation, and students’ diverse backgrounds. The study concludes that character development at Miftahussalam Madrasah is progressing yet requires more systematic planning, continuous evaluation, and stronger parental engagement. These findings contribute to the refinement of character education models in contemporary Islamic schooling contexts.